2011
DOI: 10.1002/ejic.201100289
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Polymorphs – Growth and Characterization of α‐LnNiGa4 (Ln = Y, Gd–Yb) and β‐LnNi1–xGa4 (Ln = Tb–Er)

Abstract: The single crystals of two polymorphs of LnNiGa 4 , namely, the orthorhombic α-LnNiGa 4 (Ln = Y, Gd-Yb) and, a new polymorph, the tetragonal β-LnNi 1-x Ga 4 (Ln = Tb-Er), were successfully grown by using the self-flux method. α-LnNiGa 4 (Ln = Y, Gd-Yb) is isostructural to YNiAl 4 and can be described as an edge-sharing polyhedral of Ni@Ga 7 Ln 2 (Ln = Y, Gd-Yb) along the ac-plane that is sandwiched between the square nets of the Ga atoms along the b-axis. The structure of β-LnNi 1-x Ga 4 (Ln = Tb-Er) is a dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The discovery of these two new antiferromagnetic phases with enhanced mass behavior warranted the growth of both the Ni- and Cu-containing phases to investigate the effects of varying the transition metals on the structural stability and physical properties. , We found that the latter lanthanides form α – LnNiGa 4 (Ln = Y, Gd–Yb) and β – LnNi 1‑ x Ga 4 (Ln = Tb–Er), SmCu 4 Ga 8 , and Ln(Cu,Ga) 12 (Ln = Y, Gd–Er, and Yb) . In any case, the Ni or Cu analogues were not found to adopt the SrAu 2 Ga 5 structure type. ,,, …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The discovery of these two new antiferromagnetic phases with enhanced mass behavior warranted the growth of both the Ni- and Cu-containing phases to investigate the effects of varying the transition metals on the structural stability and physical properties. , We found that the latter lanthanides form α – LnNiGa 4 (Ln = Y, Gd–Yb) and β – LnNi 1‑ x Ga 4 (Ln = Tb–Er), SmCu 4 Ga 8 , and Ln(Cu,Ga) 12 (Ln = Y, Gd–Er, and Yb) . In any case, the Ni or Cu analogues were not found to adopt the SrAu 2 Ga 5 structure type. ,,, …”
Section: Introductionmentioning
confidence: 95%
“…16 In any case, the Ni or Cu analogues were not found to adopt the SrAu 2 Ga 5 structure type. 14,15,17,18 Exploration of similar phase spaces using an Al flux resulted in the growth of LaNi 1+x Al 6-x 19 and more recently CePd 1-x Al 6-x . 20 The disorder in these compounds occurs on the same Wyckoff site that is observed to disorder in the parent phase, SrAu 2 Ga 5 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Raw data are found in the ; they also noted temperature-dependent differences in the Ce/Pd/Ga system (vide infra). 15 These conversions that occur in gallium flux reactions may possibly be linked to the change in local structure and bonding of the molten gallium solvent that occurs around 1000 K (727 °C), which was observed in both high-temperature NMR studies and synchrotron X-ray pair distribution function studies of molten gallium. 16,17 In the absence of in situ neutron diffraction facilities, we have carried out several Ce/T/Ga reactions, quenching them (by removing from the furnace and decanting the excess gallium via centrifugation to stop the reaction) above and below this transition; the products were analyzed using SEM-EDS, PXRD, and SC-XRD and are listed in Table 2.…”
Section: ■ Introductionmentioning
confidence: 99%